2013
DOI: 10.1590/s0102-311x2013000300014
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre mortalidade e estado marital: uma análise para idosos residentes no Município de São Paulo, Brasil, Estudo SABE, 2000 e 2006

Abstract: Este trabalho tem como objetivo analisar, para a população com 60 anos e mais, residente no Município de São Paulo, Brasil, a associação entre mortalidade e estado marital. Para atingir o objetivo proposto, foram utilizados os dados do Estudo SABE: Saúde, Bem-estar e Envelhecimento (SABE), realizado nos anos 2000 e 2006, e modelos de Regressão de Poisson foram estimados, levando-se, em consideração, a variação do tempo de risco de morte. No geral, os resultados indicam que, entre os idosos paulistanos do sexo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 13 publications
1
12
0
14
Order By: Relevance
“…The heterogeneity of the elderly population is directly influenced by the decline in mortality in advanced ages, gender, marital status, geographic region and people's accessibility to social and economic conditions. The longevity of humanity should be seen as a triumph of development and one of the greatest achievements of humanity (3)(4) .…”
Section: Introductionmentioning
confidence: 99%
“…The heterogeneity of the elderly population is directly influenced by the decline in mortality in advanced ages, gender, marital status, geographic region and people's accessibility to social and economic conditions. The longevity of humanity should be seen as a triumph of development and one of the greatest achievements of humanity (3)(4) .…”
Section: Introductionmentioning
confidence: 99%
“…The aging of the population's age structure and consequently a bigger relative and absolute quantitative of the population who is 60 years old and older contributed to a notable demographic change in Brazil and in the world at the end of the twentieth century (1) . In the 2010 census the elderly population reached 20.5 million people (2) in Brazil, with almost 4.8 million in the state of São Paulo.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the prevalence of NCDs in the elderly is high, especially hypertension, diabetes mellitus, cardiovascular and osteoarticular diseases (1,4) . Due to the higher prevalence of NCDs and medications, the elderly tend to use more health services than other age groups.…”
Section: Introductionmentioning
confidence: 99%
“…Já Barbosa et al (2015) encontraram 60,1% de indivíduos na mesma condição, ao estudarem idosos assistidos nos serviços de saúde pública. Esta condição também pode representar impactos a saúde uma vez que a solidão e principalmente o processo de luto e viuvez são fatores estressores que se associam à diminuição do autocuidado, contribuem para o aumento da exposição à riscos ambientais e comportamento inseguro (GOMES et al, 2013).…”
Section: Variáveisunclassified